(untitled) (Research, Society and Development, 2022)
Objective: to identify the degree of satisfaction with social support among university students in the area of health science in the city of Sergipe through the groups. Method: This is a cross-sectional, descriptive and exploratory research. The sample was non-probabilistic, for convenience, composed of 190 health sciences students from the Federal University of Sergipe. Results: satisfaction with social support was considered low by 57 (30%). The social environment at work and the relationship with university colleagues was associated with satisfaction with positively social support. Those who are part of a Student family that most talk about sex and sexuality also presented. Conclusion: Satisfaction with social support can directly interfere with physical and mental health conditions, in addition to impairing service performance and social life. The study of social support becomes a great ally in planning support strategies and promoting mental health in universities.